Current Status and Way Forward of Microwave Hybrid Heating in India: A Bibliometric Analysis - Kumar V.; Misra J.P.; Saxena K.K. (My University, 2025)
Automotive and aerospace industries are keen to employ unique techniques and novel materials to reduce weight and cost and improve part performance. The application of microwave technology in the processing of metallic materials is a relative breakthrough in this direction. Recently, microwave hybrid heating (MHH) has evolved to extend the technique's utility further. Several studies on MHH have been carried out worldwide in the last three decades, and India is the prime contributor. This article documents a systematic and bibliographic review of MHH (between 1998-2022) in the Indian scenario. For this purpose, 125 documents are chosen from Scopus Core Collection and analyzed using a bibliometric analysis tool. The research status is examined based on the time distribution of articles, geography, top-cited documents, citation mapping of journals and researchers, mapping of co-occurrence, analysis of authors' keywords, country-wise publications, and cluster assessment. The result establishes that India is dominating, followed by theUSA. Moreover, there is an increasing trend in the number of publications. A guideline is also included to revive the research community's interest to mature the process further. © 2023, National Institute of Science Communication and Policy Research. All rights reserved.